英國教師專業發展機構之初探─以教師專業發展為主 The Explore of Teacher Professional Development Agency in England - 邱亭尹 Chiu, Ting-Yin (National Changhua University of Education, 2009)
本文檢視英國教師專業發展機構─學校訓練與發展局(Training and DevelopmentAgency for Schools, 簡稱TDA)近期政策實施內容。以英國師資培育制度變革為背景脈絡；其後探究學校訓練與發展局(TDA)近期策略與目標，包含對教師、學校領導者和職員的持續專業發展規劃(Continuing Professional Development， 簡稱CPD)， 以及教師專業標準(professional standards for teachers)；最後，以英國經驗提出結論與建議。 The focus of this study is on the reviewing England's changes of teacher training system as the context to describe the professional standards of teachers, and the operation of Continuing Professional Development (CPD) programs of school teachers, leaders and staff that England government established. At last, the experience of the England's teacher training system: TDA (Training and Development Agency for Schools) will be the conclusion of the study.